Estimating earthing resistance of rod electrode using finite-element method / Mohd Nashriq Mohamad Dat - Mohamad Dat, Mohd Nashriq (2010)
Earthing is an important technology in the fields of electric power, communication, and lightning protection. The earthing electrode is used as the ground and the electric terminal which comes in various shapes from small scale like rod-shaped and plate-shaped to large scale such as ring-shaped and mesh shaped. When designing earthing, its resistance which is an index of the rise in electric potential must be known. The earthing resistance of the electrode such as a rod-shaped and a plate-shaped is computed by approximated analysis. There are methods of earthing simulation such as the tank model method or Laplace numerical analysis equation method (for example, the finite element method) used to estimate a shaped earthing resistance without analytic answer. Finite-element analysis will be used to compute earth-resistance of rod-shape electrode in both homogeneous soil and multi-layer soil models.